L'intentionnalité et le projet professionel: préalables conceptuels de recherche - Drolet, Jean-Louis (Canadian Journal of Counselling and Psychotherapy, 2011)
This study presents the significant manner in which the existential concept of intentionalitycan contribute to a better understanding of the relationship between the individual and work.The author examines certain basic postulates considered prerequisites to a furtherinvestigation into intentionality as it is expressed through the professional project.Intentionality is differentiated from intention and is defined here as a dynamic, ultimatestructure of meaning that the individual expresses through his dialectical rapport with hisenvironment